The Relationship Between Work Stress and Work Fatigue Among Laundry Workers in The Muhammadiyah University of Surakarta Area - Elvina Nadya Reswara; Denny Saptono (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Work stress and work fatigue are occupational safety and health issues frequently experienced by workers in the informal sector, including laundry workers. Physically demanding work activities, performed repetitively, along with long working hours, have the potential to increase work stress and impact work fatigue. This study aimed to determine the relationship between work stress and work fatigue among laundry workers in the area of Muhammadiyah University of Surakarta. This research used a quantitative method with an analytical observational design and a cross-sectional approach. The research population consisted of all laundry workers in the Muhammadiyah University of Surakarta area, with a sample size of 50 respondents taken using total sampling technique. Work stress data was collected using the National Institute for Occupational Safety and Health (NIOSH) questionnaire, while work fatigue was measured using the Industrial Fatigue Research Commit tee (IFRC) questionnaire. Data analysis was performed univariately and bivariately using the chi-square test. The results showed that 50% of respondents experienced high work stress and 44% experienced high work fatigue. The chi-square test results showed a p-value < 0.05, indicating a significant relationship between work stress and work fatigue among laundry workers in the Muhammadiyah University of Surakarta area. The higher the level of work stress experienced by workers, the higher the risk of work fatigue.